Do parents receive their educational investment results? Indonesian case - Edy Purwanto (Universitas Sebelas Maret, 2020)
Aside from identifying the determinants of transfers from children to parents in developing countries like Indonesia, this paper's primary purpose is to examine the effect of education level attainment on the amount of transfer from children to parents. We use the Indonesia Family Life Survey (IFLS-5) data, which covers approximately 34,000 adult individual respondents. Out of all respondents, 16,016 observations met the sample criteria of aged 15 years and older who have parents living outside the household. The result shows that 75% of children provided assistance to parents in the form of money, goods, or labor/time within a year preceding the survey. The average money transfer per year is IDR 1,030,000 (approximately 70 USD), goods transfer worth IDR 303,000 (approximately 20 USD, and 16 days of labor. The result from logistic regression analysis identifies that the determinants of transfers from children to parents are some of the children's characteristics such as education, age, marital status, work, income, and living in urban regions. In addition, from the parent's perspective, parents' characteristics that affect the transfer amount are age, health condition, and widow status.